Employee socialization process and engagement in Malaysian hotel industry - Irza Hanie, Abu Samah; Intan Maizura, Abd Rashid; Abdul Shukor, Shamsudin; Wan Ahmad Fauzi, Wan Husain; Mohammad Harith, Amlus; Nur Syafiqah, A. Rahim; Hariri, Hamzah (AIP Publishing, 2023)
Employee in the organization always the core of the activities implemented in the company. without engaged employee, organization would remain constants and there are slim chances for organization to survive in the future. Our world has viewed the importance of employee engagement in the organization that act as energy to empower all employees to boost productivity and overall performance. However, to obtain engaged employees, requires certain level of work understanding. although research on employee engagement has been growing since 90’s, however, little was known to study on the understanding before employee could engaged. This research contributes the gap by using Socialization Theory to explain the theoretical concept of employee engagement. Respondents are from selected hotel employee in northern region in Malaysia. Findings conclude that socialization proses phase 3 which is element of acquire shows significant relationship towards employee engagement of absorption and dedication (P-value< 0.05, t-value >1.645). This research is importance for researcher in the field of human resource to understand better on the construct of employee engagement and its antecedent.